Introduction to HR technologies understand how to use technology to improve performance and processes - Harris, Stacey (Kogan Page, 2021)
Technology can have huge benefits for the HR function. Whether it's saving time by streamlining processes, boosting engagement by enabling analysis of people data or improving employee development by allowing staff to access the content they need on different platforms, wherever and whenever they need it, the opportunities are vast. But with more apps, software and platforms than ever before, the volume and variety of available technologies can be overwhelming. In clear, accessible and jargon-free language, Introduction to HR Technologies enables HR professionals to know where to start when assessing what technologies are out there and which ones are worth investing in. Covering all the core areas of HR from administration and service delivery through to talent management and analytics, the book allows practitioners to identify areas where technologies can be used to drive performance and what to look for when assessing technological solutions. The book also discusses AI, machine learning and the Internet of Things and what they mean for HR. With case studies from organizations including Fedex and Macy's, Introduction to HR Technologies is an indispensable guide for HR professionals needing to get to grips with technologies and understand how to use them to add tangible value to both employees and the business as a whole." --